Perovskite Solar Cells: Poly(3, 4‐Ethylenedioxythiophene): Methylnaphthalene Sulfonate Formaldehyde Condensate: The Effect of Work Function and Structural Homogeneity on Hole Injection/Extraction Properties (Adv. Energy Mater. 6/2017). Issue 6 (22nd March 2017) - Li, Yuda; Liu, Meiyue; Li, Yuan; Yuan, Kai; Xu, Lijia; Yu, Wei; Chen, Runfeng; Qiu, Xueqing; Yip, Hin‐Lap
Abstract : PEDOT:PSS suffers from its poor structural homogeneity. In article number 1601499, Yuan Li, Xueqing Qiu, Hin‐Lap Yip, and co‐workers report a novel PEDOT:MNSF with enhanced structural homogeneity and promising performance in organic electronic devices. The branched structure of PEDOT:MNSF contributes to its hole extract property and the herringbone image arranged by ladybug indicates that this design concept will move PEDOT‐based materials toward a brilliant future.